2017
DOI: 10.22616/rrd.23.2017.010
|View full text |Cite
|
Sign up to set email alerts
|

Biological protection of conifers against Heterobasidion infection – interaction between root-rot fungus and Phlebiopsis igantea

Abstract: The biological control agent Rotstop, composed of spores of Phlebiopsis gigantea, is used for treatment of conifer stumps to reduce the spread of Heterobasidion root rot in commercial forests. Two experiments were conducted to compare the antagonistic ability of the Rotstop isolate and nine Latvian isolates of P. gigantea against root rot fungus Heterobasidion, in wood of Scots pine and Norway spruce. Billets of conifer trees were first sprayed with a spore suspension of P. gigantea and then with Heterobasidio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…If the stump surface was uncovered, Rotstop ® and P. gigantea 422 reached more than 60% efficacy based on the proportion of infected stumps and at least 65% efficacy based on the relative infected area. The results obtained about BCA efficacy based on incidence and colonized area are in agreement with previous research with Norway spruce in Finland, Sweden and Latvia [16,45,[61][62][63]. Our results showed that the covered stumps had a greater relative surface colonized by P. gigantea.…”
Section: The Effect Of Stump Cover On Heterobasidion Spp and P Gigantea Developmentsupporting
confidence: 92%
“…If the stump surface was uncovered, Rotstop ® and P. gigantea 422 reached more than 60% efficacy based on the proportion of infected stumps and at least 65% efficacy based on the relative infected area. The results obtained about BCA efficacy based on incidence and colonized area are in agreement with previous research with Norway spruce in Finland, Sweden and Latvia [16,45,[61][62][63]. Our results showed that the covered stumps had a greater relative surface colonized by P. gigantea.…”
Section: The Effect Of Stump Cover On Heterobasidion Spp and P Gigantea Developmentsupporting
confidence: 92%
“…Серед деревночагарникової рослинності хвойні характеризуються найменшою стійкістю до ураження кореневими гнилями. Коренева губка (Heterobasidion annosum s. l) є одним із найнебезпечніших збудників хвороб соснових лісів, що спричиняє окоренкову гниль і призводить до погіршення якості деревини та зниження захисних властивостей лісів (Kenigsvalde et al 2017, Gaitnieks 2020. Доведено (Chernykh 1965, Rebko et al 2008, Dyshko 2021, що в окремих осередках усихання насаджень, уражених кореневою губкою, протягом тривалого часу на високому інфекційному фоні зберігаються життєздатні дерева, які зовні не виявляють ознак захворювання.…”
unclassified